Accept or Reject: The Role of Immune Tolerance in the Development of Stem Cell Therapies and Possible Future Approaches. (October 2021) - Haworth, Richard; Sharpe, Michaela
In 2011, Goldring and colleagues published a review article describing the potential safety issues of novel stem cell-derived treatments. Immunogenicity and immunotoxicity of the administered cell product were considered risks in the light of clinical experience of transplantation. The relative immunogenicity of mesenchymal stem cells, embryonic stem cells (ESCs), and induced pluripotent stem cells (iPSCs) was being addressed through in vitro and in vivo models. But the question arose as to whether the implanted cells needed to be identical to the recipient in every respect, including epigenetically, to evade immune recognition? If so, this set a high bar which may preclude use of many cells derived from iPSCs which have vestiges of a fetal phenotype and epigenetic memory of their cell of origin. However, for autologous iPSCs, the immunogenicity reduces once the surface antigen expression profile becomes close to that of the parent somatic cells. Therefore, a cell product containing incompletely differentiated cells could be more immunogenic. The properties of the administered cells, the immune privilege of the administration site, and the host immune status influence graft success or failure. In addition, the various approaches available to characterize potential immunogenicity of a cell therapy will be discussed.